Cancer in myasthenia gravis subtypes in relation to immunosuppressive treatment and acetylcholine receptor antibodies: A Swedish nationwide register study. (28th January 2021) - Verwijst, Johanna; Westerberg, Elisabet; Punga, Anna Rostedt
Abstract: Background and purpose: The potentially increased risk of extrathymic cancers in myasthenia gravis (MG) remains uncertain. We present the occurrence of extrathymic cancer diagnoses in different MG subgroups. Methods: We conducted a nationwide Swedish register‐based cohort study, including patients who had their first MG diagnosis or first prescription of acetylcholine esterase inhibitors between the years 2006 and 2018. Timing and subtypes of cancer diagnosis in relation to MG as well as corticosteroid‐sparing immunosuppressants (CSISs) were identified from national patient, cancer and drug registers. Results: In the study population of 2812 MG patients, 92 had juvenile MG (3%), 632 had early‐onset MG (23%), 1968 had late‐onset MG (LOMG; 70%) and 120 patients had thymoma‐associated MG (TAMG; 4%). Extrathymic cancers were observed in 630 patients (22.4%). Skin cancer and cancer in the male genital organs were most common ( N = 138, respectively), followed by cancers in the female genital organs ( N = 103), digestive organs ( N = 90) and breast ( N = 80). Patients with TAMG (29.2%) and LOMG (28.4%) had the highest occurrence of extrathymic cancer. Cancer frequency was comparable between acetylcholine receptor antibody seropositive and seronegative patients. Two or more CSIS prescriptions significantly increased the frequency of cancer, especially cancers in the digestive organs ( p = 0.0026), male genital organs ( p = 0.0037) and skin ( p < 0.0001). Conclusions: Most extrathymic cancer types in MG were observed in TAMG and LOMG patients, and there was a clear correlation between CSIS exposure and cancer risk. This study sheds light on extrathymic cancers also in non‐thymoma MG. Abstract : We present the occurrence of extrathymic cancer diagnoses in different myasthenia gravis (MG) subgroups in a nationwide Swedish study. Extrathymic cancers were observed in 630 patients (22%). Most extrathymic cancer types in MG were observed in TAMG and LOMG patients.